Das modernisierte Besteuerungsverfahren in Deutschland im Vergleich zu Österreich Die verfassungsgemäße Fortentwicklung von E-Government als Herausforderung und Chance für die deutsche Finanzverwaltung - Schmidt, Christoph (Schriften zum Steuerrecht, 2021)
»The Modernized Taxation Procedure in Germany Compared to Austria« The comparative law study is dedicated to the highly topical and practice-relevant topic of digital tax enforcement and deals with its opportunities, challenges and limitations. With the developed concrete reform proposals for the German taxation procedure, the work is intended to advance the discussion on the further development of tax procedure law both from the perspective of (tax consulting) practice and from the academic perspective.